(untitled) (Transactions of the Association of European Schools of Planning, 2017)
The paper discusses the co-evolution of the EU mode of governance and the objectives of European Union cohesion policy. As EU integration proceeds, collective decision-making in an increasingly diverse political arena has become a central concern for research on EU governance. The literature on experimentalist governance suggests consensus-seeking deliberation and policy-experimentation as two key mechanisms to reduce the trade-off between overall policy responsiveness and democratic legitimacy. However, this paper argues that the inconsistencies which result from making cohesion policy deliver the Lisbon Agenda and EU 2020 objectives growth are a characteristic of meta-governance rather than of reflexive adaptation. These findings emerge from an analysis of the cohesion policy programming periods since 1988 and the parallel developments in European Union governance.